Carbon-nanotube for Transient Expression in Rice Calli - Paphawarin Pinyokham; Kamolwan Khianchaikhan; Pongsakorn Sunvittayakul; Supachai Vuttipongchaikij; Piyama Tasanasuwan; Chatchawan Jantasuriyarat (Bogor Agricultural University, Indonesia, 2022)
Transient gene expression is an important technique in gene functional analysis, protein production and in plants. However, traditional transient expression methods using Agrobacterium are time-consuming with low efficiency. In this study, we demonstrated the use of a single-walled carbon nanotube (SWCNT) to deliver 35S:mCherry:pCXSN plasmid into rice calli. This transient expression protocol used a plastic medical syringe to create the physical pressure to help the delivery of plasmid DNA into plant cells. This protocol is relatively easy to perform and low cost. The transient expression was observed under fluorescence microscopy, and the mCherry fluorescence signal was quantified. The plasmid DNA was delivered into the rice cell using a 3:1 ratio (plasmid: carbon nanotube). The result showed that the mCherry signal of carbon nanotube + plasmid DNA treatment was the highest signal at 3 days post-transformation and decreased to a lower signal at 6 days post-transformation. Moreover, the quantitative analysis of mCherry mean intensity revealed that the signal intensity of carbon nanotube + plasmid DNA treatment was the highest level, and significantly higher than the control treatments at 3 days post-transformation. Plasmid DNA can be transported easily into plant calli using this carbon nanotube transient expression protocol.